Neutrophil-Mediated Phagocytosis of Staphylococcus aureus - van Kessel, Kok P. M.; Bestebroer, Jovanka; van Strijp, Jos A. G. (Frontiers in Immunology, 2014)
For invading staphylococci, phagocytosis an killing bij human neutrophils is the biggest threat. Neutrophils are the only cells that can effectively kill staphylococci by engulfment and subsequent bombardment with proteases, amidases, antimicrobial peptides and proteins in concert with reactive oxygen species that are generated during the metabolic burst. Both complement and antibodies are crucial for effective uptake and neutrophil activation. S. aureus is not an innocent bystander in this process. It actively secretes several proteins to impair every single step in this process from receptor modulation, to complement inhibition to neutrophil lysis to protease, antimicrobial peptide inhibition and resistance to reactive oxygen species. For the design of future novel antimicrobial strategies: therapeutic antibodies, vaccines, novel antibiotics, all this should be taken into account. Still the best way to treat diseases is to help to enhance the natural defence mechanism that are already in place.